2015
DOI: 10.15171/joddd.2015.030
|View full text |Cite
|
Sign up to set email alerts
|

Galvanic Corrosion of and Ion Release from Various Orthodontic Brackets and Wires in a Fluoride-containing Mouthwash

Abstract: Background and aims. This study compared the galvanic corrosion of orthodontic wires and brackets from various manufacturers following exposure to a fluoride mouthwash.Materials and methods. This study was conducted on 24 lower central incisor 0.022" Roth brackets of four different commercially available brands (Dentaurum, American Orthodontics, ORJ, Shinye). These brackets along with stainless steel (SS) or nickel-titanium (NiTi) orthodontic wires (0.016", round) were immersed in Oral-B mouthwash containing 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Tahmasebi et al in 2015 evaluated the release of ions from wires and brackets in Oral B fluoride mouth rinse and found that NiTi wires had the highest release of nickel ions and SS wires had the highest release of chromium [25]. In our study, the release of both ions from NiTi wires was higher than that from SS wires, although some differences were observed at different time-points.…”
Section: Discussionmentioning
confidence: 44%
“…Tahmasebi et al in 2015 evaluated the release of ions from wires and brackets in Oral B fluoride mouth rinse and found that NiTi wires had the highest release of nickel ions and SS wires had the highest release of chromium [25]. In our study, the release of both ions from NiTi wires was higher than that from SS wires, although some differences were observed at different time-points.…”
Section: Discussionmentioning
confidence: 44%
“…24 In case of released copper, iron, molybdenum, and titanium ions, no significant difference was detected between various wire/bracket combinations. When released ions from these bracket/wire combinations were assessed in fluoride mouth wash, 19 besides Ni, there were significant differences between groups in terms of Cu and Fe. This conflict addresses the importance of electrolyte composition in corrosion behavior of metals.…”
Section: Discussionmentioning
confidence: 98%
“…The results are consistent with previous studies that show the increased amount of Ni release from this bracket in fluoride mouthwash and acidic artificial saliva. 19,20 It has been known that there is no proportional relation between the release of nickel ions and the nickel content of orthodontic brackets and wires. 6 The results confirm this finding, as the Ni content of Shinye bracket is less than that of Dentaurum bracket and is close to ORJ and American Orthodontics brackets (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The three metallic orthodontic bracket types were first placed in an acetone solution for 2 minutes for surface cleansing, 17 and the pH of each mouthwash and the DW was measured using pH meter (JENWAY, model 3320, Cyprus) as shown in Figure 1. The brackets were subdivided into five subgroups (for each main type) according to the mouthwash, 10 per each subgroup and dipped separately in a 20 mL glass beaker containing 15 mL of the specific mouthwash and kept in incubator at 37°C for 45 days.…”
Section: Methodsmentioning
confidence: 99%
“…The use of mouthwashes is associated with ions released in saliva. In vitro studies [13][14][15][16][17][18] were performed to estimate the concentrations of different ions, such as Ni, Cr, Cu, Fe, and Mn in chemical (fluoridated and nonfluoridated) and some herbal mouthwashes. To the best of authors' knowledge, gold-plated bracket has not been investigated in regard to ion release.…”
Section: 5005/jp-journals-10024-2214mentioning
confidence: 99%